Role of clinical pharmacist in drug utilization evaluation, medication adherence and pharmacovigilance - Saji, Sanju T.; V. V., Prasanth; Dagariya, Rishab Kumar (International Journal of Basic & Clinical Pharmacology, 2024)
A series of systematic, criterion-based drug evaluation known as Drug utilization review are conducted on a regular basis to ensure that medication is utilized appropriately. It’s a mean of learning more about the issues brought on by drug usage, if done properly, may help to solve the issues. Medication adherence generally refers to a patient’s ability to take prescription drugs as directed and their continued use of those drugs. The increasing body of research linking medication non adherence to unfavorable outcomes and increased healthcare cost has raised concerns among clinicians, healthcare institutions, and other stakeholders. Pharmacovigilance, in which the procedures keeping an eye on the assessing adverse medication reactions, is essential to clinical practice, public health and efficient drug regulating system. Aim of the study was wo study about the role of pharmacist in drug utilization review, medication adherence and pharmacovigilance.